Female Genital Fistula Repair Performance of Ad-din Hospitals 2013-2018 - Yesmin, Nahid; Yesmin, Farzana; Podder, Sheela; Ghose, Lucky (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The aim of this paper is to document the female genital fistula repair services at Ad-din hospitals and to describe the etiology of fistula cases and care outcomes. Methods: Data from fistula services provided by Ad-din Hospitals in Dhaka, Khulna and Jashore were regularly captured using an aggregated DHIS2 established by the Fistula Care Plus project since December 2013. In January 2017, the FC+ project introduced a Safe Surgery Tool Kit (SST) to capture and analyze individual client data. Results: During the period of data collection, the Ad-din Hospitals have provided repair surgery to 259 clients including 134 female genital fistula cases, and 95 cases of complete perineal tear. Out of the fistula cases, 25% were iatrogenic. There is a trend of increasing iatrogenic fistula over this period. Over the data collection period, the closed and dry rate among fistula cases was 80%. Conclusions: Ad-din hospitals are a major provider of fistula surgery to women suffering from fistula in Bangladesh. Ad-din institutions are linked with social financing and community health system. Ad-din community networks made significant contribution in case identification at field level, case referral and community based rehabilitation of fistula cases.